Mating system and genetic structure of two populations of white spruce ( Picea glauca) in eastern Newfoundland - Innes, David J.; Ringius, Gordon G. (Canadian Journal of Botany, 1990)
Allozyme variation at four polymorphic enzyme loci (Pgi-1, Pgi-2, Pgm, Gdh) was used to study genetic variation and mating system in a sheltered (inland) and an adjacent exposed population (coast) of white spruce (Picea glauca (Moench) Voss) in eastern Newfoundland. Despite habitat differences, the two populations showed only small differences in allele frequency for the maternal trees, their progeny, and the estimated pollen pool. Three of the four single-locus estimates of outcrossing rate (t s ) for the inland population were significantly less that t = 1.00, with an average value of t s = 0.81. Two of the four single-locus estimates of outcrossing rate in the coast population were significantly less than t = 1.00 and the average for the four loci was 0.71. The multilocus estimates of outcrossing rate (t m ) for the inland and coast populations were 0.76 and 0.70, respectively, and both estimates were significantly less than t = 1.00. This level of selfing is higher than that observed for most other conifer species. Key words: genetics, mating system, population genetics, outcrossing, selfing, white spruce.